Some Remarks on Design of LED Lamps and their AC Direct Drivers - Filus, Zdzislaw; Checinski, Jacek (Elektronika ir Elektrotechnika, 2019)
Many examples of capacitorless and inductorless drivers used to power LED lamps directly from the AC mains use complicated circuitry in the form of a dedicated integrated circuit which is designed for a particular multistring lamp in order to obtain the value of the power factor very close to 1 and high efficiency of the whole unit. However, the authors of such descriptions do not provide any details concerning the optimum choice of the number of strings in a LED lamp and the number of LEDs in each string. The aim of this work is to show that acceptable values of both electrical parameters mentioned above can be obtained using a LED lamp with just one or two strings. Some formulae and results of their numerical analysis for the 230 V 50 Hz mains are presented, thanks to which designers of LED lamps and their AC direct drivers may easily estimate the optimum conduction voltage of a LED string or the number of single LEDs in a string.